Ocean acidification and the Permo-Triassic mass extinction - Clarkson, M. O.; Kasemann, S. A.; Wood, R. A.; Lenton, T. M.; Daines, S. J.; Richoz, S.; Ohnemueller, F.; Meixner, A.; Poulton, S. W.; Tipper, E. T. (Science, 2015)
Ocean acidification and mass extinction The largest mass extinction in Earth's history occurred at the Permian-Triassic boundary 252 million years ago. Several ideas have been proposed for what devastated marine life, but scant direct evidence exists. Clarkson et al. measured boron isotopes across this period as a highly sensitive proxy for seawater pH. It appears that, although the oceans buffered the acidifiying effects of carbon release from contemporary pulses of volcanism, buffering failed when volcanism increased during the formation of the Siberian Traps. The result was a widespread drop in ocean pH and the elimination of shell-forming organisms. Science , this issue p. 229